Recent Advances in Biginelli Reaction using Nanoparticles, Zeolites and Metal Compounds as Catalyst: A Concise Review - Bhatt, Bhaktiben R.; Dixit, Bharat C.; Kataria, Vipul B.; Dixit, Ritu B.; Saiyad, Shaffiq (Letters in Organic Chemistry, 2024)
The year 1891 is considered as a historic year in chemical science due to the introduction of novel heterocyclic compounds by P. Biginelli. The classical Biginelli reaction offers 3,4- dihydropyrimidin-2(1H)-ones/thiones in occupancy of acids like Broansted and Lewis. Multifaceted Dihydropyrimidones (DHPMs) have gained much importance due to their high biological activities. Several nanoparticles, zeolites and metal compounds are disclosed to improve the yield of this product. This review subsumes the evolution and effectiveness of catalysts. It summarises the main synthetic routes which are known to obtain DHPMs using these catalysts. The majority of these catalysts delivered satisfying catalytic activity which was more than 80% in the vicinity of producing Biginelli adducts. We hope this review article will be useful to researchers in terms of obtaining higher yields in a shorter time using easily available and reusable catalysts.
Keywords: metal compound catalyst